Prognostic impact of extranodal involvement in diffuse large B‐cell lymphoma in the rituximab era - Takahashi, Hiroyuki; Tomita, Naoto; Yokoyama, Masahiro; Tsunoda, Saburo; Yano, Takahiro; Murayama, Kayoko; Hashimoto, Chizuko; Tamura, Kazuo; Sato, Kazuya; Ishigatsubo, Yoshiaki (Cancer, 2012)
BACKGROUND: Extranodal involvement is considered a poor prognostic factor for patients with diffuse large B‐cell lymphoma (DLBCL); however, the prognostic impact of specific sites of involvement has not been fully elucidated. METHODS: The authors retrospectively analyzed 1221 patients treated uniformly with standard R‐CHOP therapy between 2003 and 2006. Patients with distinct forms of DLBCL such as intravascular lymphoma, primary effusion lymphoma, pyothorax‐associated lymphoma, primary central nervous system lymphoma, and intraocular lymphoma were also excluded. The authors evaluated 26 extranodal sites of involvement with respect to prognostic impact. The median age was 64 years (range, 15‐91 years). RESULTS: Univariate analysis revealed that patients with involvement of specific extranodal sites had significantly worse overall survival (OS) than did patients without such involvement; these sites included nasal cavity, paranasal sinus, lung, pleura, small intestine, peritoneum, liver, pancreas, stomach, spleen, adrenal gland, testis, bone, bone marrow, peripheral blood, skin, and subcutaneous tissue. Patients with Waldeyer ring involvement had significantly better OS. Multivariate analysis revealed that patients with the involvement of the pleura (P < .001), small intestine (P = .015), peritoneum (P = .002), adrenal gland (P < .001), testis (P = .005), bone marrow (P < .001), and peripheral blood (P = .002) had significantly worse OS, whereas those with Waldeyer ring involvement had significantly better OS (P = .038). Subgroup analysis with the nodal and/or Waldeyer patient group also showed prognostic impact of Waldeyer ring by multivariate analysis (relative risk, 0.3; P = .04). CONCLUSIONS: Extranodal involvement affects the prognosis of patients undergoing R‐CHOP therapy for DLBCL. Cancer 2012. © 2011 American Cancer Society. Retrospective analysis of 1221 diffuse large B‐cell lymphoma patients who have been uniformly treated with R‐CHOP therapy detects prognostic impact for 8 extranodal sites. Waldeyer ring involvement has significantly better prognosis and should be treated as an extranodal lesion.